Hydrodynamic Coefficients for Array of Tubular Cylinders - Kurian, V.J. (2014)
Hydrodynamic coefficients for groups of tubular cylinders subjected to regular waves were experimentally investigated in this study. The experiments were carried out at Universiti Teknologi PETRONAS wave tank. The experimental hydrodynamic forces on tubular cylinders were measured using wave force sensors, while the theoretical values were estimated using Morison equation. The effects of neighboring cylinders, spacing between the pipes, wave frequency and wave amplitude on the hydrodynamic coefficients of tubular cylinders were analyzed. In this study, the model cylinders were fixed to the soffit of the wave tank bridge as cantilevered beams. The tubular cylinders covered in this study are 1.23 m long galvanized steel pipes with 34 mm diameter and 2.5 mm wall thickness. The immersed length of the cylinder was 850 mm. The pipes were subjected to regular waves with maximum wave height of 100 mm, and the Keulegan- Carpenter number (KC) varied from 9.25 to 14.97. The obtained inertia and drag coefficients are in fair agreement with API and PTS specifications.